The Traces of Forensic Linguistics in the Juristic Texts - مصطفی جباری; حسین رضویان (مطالعات فقه و حقوق اسلامی, 2015)
Forensic linguistics as a new interdisciplinary approach was introduced in the late twentieth century. One of the aspects of this branch of science is the analysis and interpretation of legal texts. This paper seeks to show that some jurists, consciously or not were aware of some aspects of forensic linguistics and applied it in interpretation of a number of phrases and sentences. Examples presented here have been used to confirm this claim. The examples and many other examples in juristic books show that Islamic jurists recognized capability of multiple interpretations in some juristic sentences and understood its effects and consequences. This is why a few jurists have questioned a number of orders. Using a linguistic approach, the study of jurists' different interpretations in the samples suggests that the jurists have used pragmatic techniques such as inference, action verbs, speech acts, cultural background knowledge and the local interpretation principle, in their interpretation and explanation. The implicit and indirect references to new and specialized concepts and terms â not like the terms in modern Linguistics- such as lexical ambiguity, structural ambiguity, referring expression and determining its reference is obvious. Existence of such evidences in the texts of Islamic jurisprudence confirms the hypothesis that there is a trace of Forensic linguistics in Islamic jurisprudence and Islamic jurists' interpretations.